Mudanças no mundo dos trabalhadores: os pescadores profissionais de Guaíra/ PR (1970-2011) - Paula, Cátia Franciele Sanfelice de (2012)
This thesis discusses the changes experienced by fishermen caused by structural changes resulting from the formation of Itaipu Lake and the opening of a navigation channel on the Parana River, in Guaíra/PR. The changes caused by these builds have imposed pressure limits on the life and work of the fishermen, who have they have organized themselves to resist and to fight them. Thus, we try to understand how fishermen got togetherformation a social movement against other social subjectsthat representing different projects since the 1980s, a period that the written and oral sources allowed us to cover. In particular, we discuss how the Brazilian state has intervened in this historic process through practices and projects that impact on fishermen. Among the most relevant projects we approach the attempt to involve fishermen with the industrialization of fishing. In this direction, we discuss the invested capital, mediated by the state, about the life and work of fishermen creating mechanisms that limit andoppose their continued survival through fishing.